Circumpolar Deep Water Impacts Glacial Meltwater Export and Coastal Biogeochemical Cycling Along the West Antarctic Peninsula - Cape, Mattias R.; Vernet, Maria; Pettit, Erin C.; Wellner, Julia; Truffer, Martin; Akie, Garrett; Domack, Eugene; Leventer, Amy; Smith, Craig R.; Huber, Bruce A. (Frontiers in Marine Science, 2019)
Warming along the Antarctic Peninsula has led to an increase in the export of glacial meltwater to the coastal ocean. While observations to date suggest that this freshwater export acts as an important forcing on the marine ecosystem, the processes linking ice-ocean interactions to lower trophic-level growth, particularly in coastal bays and fjords, are poorly understood. Here, we identify salient hydrographic features in Barilari Bay, a west Antarctic Peninsula fjord influenced by warm modified Upper Circumpolar Deep Water. In this fjord, interactions between the glaciers and ocean act as a control on coastal circulation, contributing to the redistribution of water masses in an upwelling plume and a vertical flux of nutrients towards the euphotic zone. This nutrient-rich plume, containing glacial meltwater but primarily composed of ambient ocean waters including modified Upper Circumpolar Deep Water, spreads through the fjord as a 150-m thick layer in the upper water column. The combination of meltwater-driven stratification, long residence time of the surface plume owing to weak circulation, and nutrient enrichment promotes phytoplankton growth within the fjord, as evidenced by shallow phytoplankton blooms and concomitant nutrient drawdown at the fjord mouth in late February. Gradients in meltwater distributions are further paralleled by gradients in phytoplankton and benthic community composition. While glacial meltwater export and upwelling of ambient waters in this way contribute to elevated primary and secondary productivity, subsurface nutrient enhancement of glacially-modified ocean waters suggests that a portion of these macronutrients, as well any iron upwelled or input in meltwater, are exported to the continental shelf. Sustained atmospheric warming in the coming decades, contributing to greater runoff, would invigorate the marine circulation with consequences for glacier dynamics and biogeochemical cycling within the fjord. We conclude that ice-ocean interactions along the Antarctic Peninsula margins act as an important control on coastal marine ecosystems, with repercussions for carbon cycling along the west Antarctic Peninsula shelf as a whole.